S92 Remote monitoring enabled evaluation of risk and physiological response to therapeutic escalation and clinical worsening in patients with pulmonary hypertension. (11th November 2022) - Middleton, JT; Binmafooz, S; Zafar, H; Patel, J; Giri, D; Battersby, C; Toshner, M; Reddy, A; Lewis, R; Durrington, C; Swift, A; Condliffe, R; et al.
Abstract : Background: In patients with pulmonary arterial hypertension (PAH) hospital-based risk stratification is used to aid decision making and guide treatment. Risk stratification based on remote monitored parameters may facilitate early evaluation of clinical efficacy following treatment change or indicate clinical stability/deterioration, thereby permitting early intervention. Methods: Patients with pulmonary hypertension were identified from the ASPIRE database (6/YH/0352). Univariate Cox Regression and stepwise forward multivariate analysis were undertaken in a derivation cohort (n=3832) to identify parameters associated with mortality. Mortality weighted z-scores of age, incremental shuttle walk test (ISWT), heart rate (HR) and total pulmonary resistance (TPR) were summed to give an individual remote risk score value and LOESS regression used to determine risk thresholds. Patients enrolled in FIT-PH (NCT04078243 ) were implanted with a pulmonary artery pressure (CardioMEMS, Abbott) and insertable cardiac monitors (LinQ, Medtronic) and remote monitored physiology observed following clinically indicated therapeutic escalation (TE) and clinical worsening events (CWE). Results: Multivariate analysis of the derivation cohort demonstrated that ISWT, HR and TPR had statistically significant relationships to mortality. Survival analysis demonstrated increased mortality with each decile of baseline risk score (p<0.01). In the validation cohort of patients with PAH (n=590), remote risk score thresholds identified low-, intermediate-low-, intermediate-high- and high-risk groups with Kaplan-Meier estimated 1-year mortality of 4.4%, 8.0%, 10.3% and 17.8% respectively (p<0.001 for between group comparisons, figure 1A ) that were consistent COMPERA 2.0 risk stratification (Cohen's weighted Kappa 0.61). In patients with remote monitoring devices implanted, following TE, mean pulmonary artery pressure and TPR were reduced and cardiac output (CO) and physical activity increased compared to baseline at days 7, 4, 22 and 42 respectively (p<0.05). The developed remote risk score was improved following TE (p<0.0001, figure 1B ) and worsened at the time of a CWE (p<0.05) consistent with established measures of risk (WHO FC, right ventricular ejection fraction, ISWT and NTpro-BNP). Conclusion: A remote risk score of mortality-associated parameters accurately categorised patients as low-, intermediate-low-, intermediate-high- and high-risk. Implementation of this score, to daily remote monitored data, identified improvement following TE and deterioration with CWE.